Are neurasthenia and depression the same disease entity? An electroencephalography study - Ge Dang; Lin Zhu; Chongyuan Lian; Silin Zeng; Xue Shi; Zian Pei; Xiaoyong Lan; Jian Qing Shi; Nan Yan; Yi Guo; Xiaolin Su (BMC Psychiatry)
Abstract Background The neurasthenia–depression controversy has lasted for several decades. It is challenging to solve the argument by symptoms alone for syndrome-based disease classification. Our aim was to identify objective electroencephalography (EEG) measures that can differentiate neurasthenia from major depressive disorder (MDD). Methods Both electronic medical information records and EEG records from patients with neurasthenia and MDD were gathered. The demographic and clinical characteristics, EEG power spectral density, and functional connectivity were compared between the neurasthenia and MDD groups. Machine Learning methods such as random forest, logistic regression, support vector machines, and k nearest neighbors were also used for classification between groups to extend the identification that there is a significant different pattern between neurasthenia and MDD. Results We analyzed 305 patients with neurasthenia and 45 patients with MDD. Compared with the MDD group, patients with neurasthenia reported more somatic symptoms and less emotional symptoms (p < 0.05). Moreover, lower theta connectivity was observed in patients with neurasthenia compared to those with MDD (p < 0.01). Among the classification models, random forest performed best with an accuracy of 0.93, area under the receiver operating characteristic curve of 0.97, and area under the precision-recall curve of 0.96. The essential feature contributing to the model was the theta connectivity. Limitations This is a retrospective study, and medical records may not include all the details of a patient’s syndrome. The sample size of the MDD group was smaller than that of the neurasthenia group. Conclusion Neurasthenia and MDD are different not only in symptoms but also in brain activities.